World anthropologies: A Portuguese-Brazilian conversation - Feldman-Bianco, B.; Vale de Almeida, M. (American Anthropologist, 2018)
Bela Feldman-Bianco (UNICAMP, Brazil; Figure 1) and Miguel Vale de Almeida (ISCTE, Portugal; Figure 2) are both members of the special advisory board of the World Anthropologies section of American Anthropologist. In 2016, section editor Virginia R. Dominguez checked in with the entire advisory board, asking for suggestions and explaining that she was contemplating a different set of genres. One such genre was a mutual interview, and she gave the example of Bela and Miguel possibly interviewing each other in person, via email, Skype, or live chat, or any combination of these, and either in Portuguese or English. Bela and Miguel agreed right away but were only able to do this in July and August 2017. That the mutual interview proved substantive and gratifying to all of us is a testament to the richness of their experiences both inside and outside of the academy. The mutual interview was conducted in Portuguese, and Virginia translated the interview into English (and, of course, ran it by the authors). Their words reflect two lives well lived, two sets of strategic choices well made, and two colleagues who frankly exemplify the very idea of engaged anthropology.